POLITICAL TRANSFORMATIONS IN KYRGYZSTAN (1991-2006) - ELEBAEVA, Aynura; PUKHOVA, Margarita (CENTRAL ASIA AND THE CAUCASUS, 2007)
Since the early 1970s, those studying the transformation processes in totalitarian and authoritarian regimes have been busy identifying the features found in all transition models and the fac-tors determining the trends and rates of democratic changes. Western political scientists (D. Ros-tow, F. Schmitter, O’Donnell, S. Huntington, and others) who have been working on the theory of democratic transition regarded the political process as common to all societies and insisted that all transition states would go through the same stages: preparatory (liberalization), decision-making (democratization), and acceptance (socialization).1 At the preparatory stage, political forces clash: the new elite mobilizes all the social strata dis-satisfied with the old regime to carry out concerted actions that lead to a protracted and bitter political struggle. Political forces rally around two opposing banners.2 Instability is an inevitable result, and economic and social crises follow suit. There are no attempts to set up a democratic regime at the first stage; it produces a technically democratic order (a so-called paternalist democracy). In the absence of a strong opposition, an authoritarian regime may survive for a long time. At the second stage, the main political forces achieve a compromise, which makes it possible to destroy the authoritarian order and set up democratic institutions in its stead. As members of the new parliamentary institutions, the opposition has the opportunity to join in the decision-making. At the third stage, the compromise is sealed and the democratic forces become consolidated. The pace of change out-lined above and the choice of roads leading to democracy depend on the alignment of the key political forces. An analysis of the transition models reveals that the democratization experience in the states, which, according to Samuel Huntington, will hardly become democratic (Central Asian countries are among them),3 should be summarized. We shall use the political process in independent Kyrgyzstan to identify the specific features and stages of its political transformation.